Mallomonas paraperfossa sp. nov. (Chrysophyceae, Synurales), a new species from the shallow ephemeral ponds in the steppe zone of the Southern Urals, Russia - Ignatenko, Marina; Gusev, Evgeniy; Yatsenko-Stepanova, Tatyana (Phytotaxa, 2024)
This paper describes a new species of Mallomonas, discovered in small ephemeral waterbodies of the steppe zone of the Southern Urals (Russia). The species description is based on scale morphology studied using scanning and transmission electron microscopy. Mallomonas paraperfossa sp. nov. is most similar to M. perfossa from the section Pseudocoronatae. A comparison was also made with the species M. lelymene and M. sabulosa. The scales of M. paraperfossa are characterized by the presence of rimmed depressions and papillae, randomly located on the shield, and wide and raised anterior flanges with parallel, evenly spaced ribs.